Mobile development with .NET MAUI. (Packt Publishing, 2022)
The .NET multi-platform app UI is a cross-platform framework to create innovative mobile and desktop applications with C# and XAML. One can develop apps using .NET MAUI that runs on Android, iOS, macOS, and Windows and add platform-specific source code and resources. As part of learning in this course, you will begin with a cursory introduction to the .NET MAUI concepts and features and their applications. You will learn.NET MAUI basics and design a simple API with the .NET Core. Next, you will learn to use an API in a .NET MAUI application, understand XAML controls, and write clear syntax. You will then learn to implement styles in a .NET MAUI application and utilize the MVVM (Model-View-ViewModel) pattern with the MVVM community toolkit. You will learn to use SQLite with a random mobile application. You will also learn to secure a mobile app using authentication and authorization protocols. Finally, you will learn to create your first Minimal API. Upon completing the course, you will comprehensively learn to create your mobile applications using .NET MAUI. You will independently advance your Visual Studio coding skillsets and learn to build innovative mobile apps using .NET MAUI. What You Will Learn Build interfaces with XAML (Extensible Application Markup Language) Develop and publish Minimal API with .NET Core Use various MAUI controls and MAUI layouts Use the MVVM pattern and community toolkit Implement .NET MAUI authentication Utilize an API in .NET MAUI app and secure it using JSON web tokens Audience This course is aimed at anyone interested in learning .NET MAUI and making cross-platform mobile applications. To take this course, you will need to know C#. Even if you do not have much exposure to the .NET development stack, this course is beginner-friendly and offers many development tips. You will also need a capable machine to run Visual Studio 2022 and mobile emulators. About The Author Trevoir Williams: Trevoir Williams is a software engineer and part-time lecturer. With a master's degree in computer science, he has spent over a decade teaching web, software, and database development courses. He also has extensive industry experience in web application development, Azure Cloud System, and server administration. He enjoys teaching IT and development courses and hopes to impart knowledge of the latest developments in industry standards and techniques to his students.